PENGARUH HIPERTENSI TERHADAP KEJADIAN STROKE ISKEMIK DAN STROKE HEMORAGIK DI RUANG NEUROLOGI DI RUMAH SAKIT STROKE NASIONAL (RSSN) BUKITTINGGI TAHUN 2011 - Irwana Usrin (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Ischemic stroke is a disease that begins with a series of changes in the brain which is attacked so that the blood supply to brain will be hampered, if it is not treated immediately it will end with the death of the brain. Incidence of ischemic stroke is about 70-85% of the total incidence of stroke. Hypertension is a major risk factor for the ischemic stroke. The higher patient’s blood pressure is, the greater stroke possibility, because hypertension can accelerate hardening of the arteries and lead to the destruction of fat in the smooth muscle cells so that it accelerates the process of atherosclerosis. This study aimed to determine the effect of hypertension on the incidence of ischemic stroke in neurology room at National Stroke Hospital Bukittinggi in 2011. Type of research is observational study with cross-sectional design. Population is the stroke inpatient in neurology room at National Stroke Hospital Bukittinggi from January through December in 2011 with 510 cases. Sample is the stroke inpatient in neurology room at National Stroke Hospital Bukittinggi which fulfilled eligible inclusion criteria with 244 cases. The sample consists of 146 ischemic stroke patients and 98 hemorrhagic stroke patients. Data analysis was conducted by the steps of univariate, bivariate and mutivariat analysis by using multiple logistic regression method. The results showed that the proportion of incident ischemic stroke in neurology room at National Stroke Hospital Bukittinggi was large enough that is 59.8% of the total cases of stroke. Hypertension is found significantly affect the incidence of ischemic stroke after controlled by diabetes mellitus status with Odds Ratio (OR) of 8.462, it meant that the risk of ischemic stroke among patient with hypertension would be 8 times greater than patient without hypertension  after adjusted by diabetes mellitus status (95% CI 3.780; 18.944).